Systems, transfer, and fields: Evaluating a new approach to energy instruction. Issue 10 (8th May 2019) - Fortus, David; Kubsch, Marcus; Bielik, Tom; Krajcik, Joseph; Lehavi, Yaron; Neumann, Knut; Nordine, Jeffrey; Opitz, Sebastian; Touitou, Israel
Abstract: Energy is a central concept in science in every discipline and also an essential player in many of the issues facing people everywhere on the globe. However, studies have shown that by the end of K‐12 schooling, most students do not reach the level of understanding required to be able to use energy to make sense of a wide range of phenomena. Many researchers have questioned whether the conceptual foundations of traditional approaches to energy instruction may be responsible for students' difficulties. In response to these concerns, we developed and tested a novel approach to middle school physical science energy instruction that was informed by the recommendations of the Framework for K‐12 Science Education (National Research Council, 2012a) and the Next Generation Science Standards (NGSS) (NGSS Lead States, 2013). This new approach differs substantially from more traditional approaches to energy instruction in that it does not require energy forms and it emphasizes connections between energy, systems, and fields that mediate interaction‐at‐a‐distance. We investigated student learning during this novel approach and contrasted it with student learning within a comparable unit based on a more traditional approach to energy instruction. Our findings indicate that students who learned in the new approach outperformed students who learned in the traditional approach in every quantitative and qualitative aspect considered in this study, irrespective of their prior knowledge of energy. They developed more parsimonious knowledge networks in relation to energy that focused primarily around the concept of energy transfer. This study warrants further investigation into the value of this new approach to energy instruction in both middle and high school.